1999
DOI: 10.1021/om980728c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Allyl(β-ketoiminato)palladium(II) Complexes:  New Precursors for Chemical Vapor Deposition of Palladium Thin Films

Abstract: Treatment of -ketoiminates with [(allyl)Pd(µ-Cl)] 2 affords volatile, air-stable allyl( -ketoiminato)palladium(II) complexes. The structure of [(methallyl)Pd(Phacac)] (Phacac ) MeCOCHCMeNPh) was determined by single-crystal X-ray diffraction. In solution 1 H NMR analyses indicate either a direct rotation of a planar allyl ligand about the allyl-palladium axis or a solvent-assisted exchange process involving the transient formation of a monodentate ketoiminato ligand. The physical properties of the complexes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…1 the NSC Regional Instrumentation Center at National Cheng Kung University, Tainan, Taiwan. The ketoimine ligands HOC(CF 3 )=CHCR=NMe, (keim1)H with R = Me and (keim2)H with R = CF 3 , were obtained via condensation of b-diketone with amine RNH 2 in the presence of montmorillonite K10 [32], while the Ru source reagent [Ru(COD)Cl 2 ] x was prepared according to the literature method [33]. All reactions were performed under nitrogen using anhydrous solvents or solvents treated with appropriate drying reagents.…”
Section: Methodsmentioning
confidence: 99%
“…1 the NSC Regional Instrumentation Center at National Cheng Kung University, Tainan, Taiwan. The ketoimine ligands HOC(CF 3 )=CHCR=NMe, (keim1)H with R = Me and (keim2)H with R = CF 3 , were obtained via condensation of b-diketone with amine RNH 2 in the presence of montmorillonite K10 [32], while the Ru source reagent [Ru(COD)Cl 2 ] x was prepared according to the literature method [33]. All reactions were performed under nitrogen using anhydrous solvents or solvents treated with appropriate drying reagents.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these results, similar types of CVD palladium compounds were developed, including a series of Pd-b-diketoiminate-and -imino-alcoholate species. 23,25 It was found that the usage of asymmetrical bdiketonate ligands provides the possibility to increase the volatility and decrease the melting point. 26 Despite the so far investigated precursors, there is still need for palladium compounds containing an asymmetrical bdiketonate ligand without having halogenated groups such as CF 3 , which is, however, challenging since the respective metalorganic complexes only possess low vapor pressures, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Pure and multimetallic films for these applications are commonly obtained by vacuum processes such as sputtering [12][13][14], electron beam evaporation [4,15], chemical vapor deposition [16,17], and atomic layer deposition [18]. Through these techniques the film thickness, deposition rates, and microstructure can be controlled.…”
Section: Introductionmentioning
confidence: 99%